Grouper DNA barcoding studies in Indonesia: A short review - Nanda Muhammad Razi; Zainal A. Muchlisin; Siti Maulida; Mutia Ramadhaniaty; Firman M. Nur; Adrian Damora; Sumarni Laila Buang Manalu; Nur Fadli (Depik, 2021)
Indonesia is recognized as one of the territories that have the highest reef fish biodiversity in the world. One of the commercially valuable fish in this area is the groupers (locally name "kerapu"). At least 76 grouper species have been reported in Indonesian waters, with three species were categorized into "vulnerable", five species "Data Deficient", and 68 species under the "Least Concern" category based on IUCN classification. The increasing exploitations rate had been reported caused the grouper stocks in Indonesia to decrease and threatened extinction. However, only limited scientific data is available regarding the grouper in Indonesia, including their identification. In most fish landing sites across Indonesia, the groupers are morphologically identified and recorded as "kerapu" to replace their scientific species names. Accurate species identification is essential in designing appropriate and sustainable management of fisheries resources. One of the tools that have been used in fish identification is DNA barcoding. In the last two decades, this molecular method has been applied to identify many fish groups globally, including grouper fish. This study reviewed the DNA barcoding approach in grouper identification in Indonesia based on the available literature.Keywords:DNA barcodingGrouperMolecular TaxonomyFisheriesIndonesia